Study of tendency of psychology students to addiction based on personality characteristics (neo) - Hamzeh Ahmadian; Changiz Rostami (Kurdistan University of Medical Sciences, 2016)
Introduction and Aims: Drug addiction is considered as a disease and one of the four major crisis in the world (environmental crisis, poverty, nuclear threat and drugs) and this issue has become complex in Iran due to the presence of young population. This study was conducted to predict students' tendency to addiction model based on personality factors (NEO). Materials and Methods: The study was descriptive - correlational and the sample consisted of 220 undergraduate and graduate psychology students at Islamic Azad University in Sanandaj, in the academic year 2014-2015 who were selected using the convenience sampling method. Research tool was a five-factor model of personality NEO-FFI, and addiction potential scale of Ahvaz (LAP). Data analysis was conducted using SPSS-16 and LISERL software was utilized for path analysis. Results: Regression analysis results showed that among the exogenous variables, extroversion and conscientiousness with regression coefficient of -0.15 and 0.37 had a direct significant effect on tendency to addiction. Conclusion: The results suggested that extroversion was a good predictor for students’ tendency to drug abuse. Therefore, education can help in the field of prevention of drug dependence.